EFFECT OF FREEZE-DRIED SUPER RED DRAGON FRUIT ANTHOCYANIN DISCLOSING SOLUTION ON DENTAL PLAQUE INDEX - Yuslianti, Euis Reni; Faramayuda, Fahrauk; Nurhalizah, Dinda Siti (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Accumulation of dental plaque can cause of dental and oral health problems such as caries and periodontitis. Dental plaque is colorless so it is difficult to see visually. Super red dragon fruit can be an alternative disclosing solution because it contains. Objectives: The purpose of this research was to determine the content and the effect of anthocyanin disclosing solution freeze dry super red dragon fruit on dental plaque index. Methods: This research is a type of the Experimental Laboratory and Quasi Experimental design research with post-test control group design method. Thirty samples were used and there were three treatment groups: the application of aquadest, super red dragon fruit disclosing solution, and synthetic disclosing solution. Super red dragon fruit freeze dry was tested for antioxidants and tested total anthocyanin levels using the pH difference method at Unjani Pharmaceutical Laboratory. Research on plaque index examination was carried out in the Integrated Dentistry Laboratory Unjani. Dental plaque index assessment is measured using PHPI (Patient Hygiene Performance Index) method. Data were analyzed using Kruskall Wallis and Mann-Whitney tests (p<0.05). Results: The results showed an anthocyanin content of 9.0764 mg/100 g and a significant difference in the anthocyanin disclosing solution freeze dry treatment of super red dragon fruit on the dental plaque index with a value of p = 0.000. Conclusion: In conclusion this research indicates that the freeze-dried super red dragon fruit disclosing solution contains anthocyanin and has an effect on the dental plaque index. This shows the potential of anthocyanin disclosing solution freeze dry super red dragon fruit can be used to detect and control dental plaque, but further research is needed to determine the length of time attached to anthocyanin disclosing solution super red dragon fruit to the tooth surface